Characterization and mitigation of gene expression burden in mammalian cells - Timothy Frei (Nature Portfolio, 2020)
The design of genetic networks in mammalian cells is still slow and often fails. Here the authors show that miRNA-based incoherent feedforward loop circuits can be used to alleviate cellular burden.